Integrating Islamic Family Law Into National Legal Systems: A Policy Analysis of Pancasila's Justice Value in Religious Court Administration - Nur Hakima Akhirani Nasution; Erwin Hamonangan Pane (Jurnal Mamangan, 2023)
This study examines the integration of Islamic family law within Indonesia's national legal framework through the lens of Pancasila's justice values in religious court administration. As Indonesia's largest judicial institution handling Islamic family matters, religious courts face significant challenges in harmonizing Islamic legal principles with the constitutional foundation of Pancasila. Employing a quantitative research methodology, this study surveyed 284 stakeholders including religious court judges, legal practitioners, policymakers, and legal scholars across multiple jurisdictions to assess perceptions of Pancasila justice value implementation, institutional effectiveness, and integration challenges. Data were collected through structured questionnaires measuring five dimensions: understanding of Pancasila justice values, integration effectiveness, administrative performance, stakeholder satisfaction, and systemic challenges. Statistical analyses including descriptive statistics, chi-square tests, and correlation analyses revealed significant findings. Results indicate that 78.5% of respondents demonstrate high understanding of Pancasila values, yet only 64.2% perceive effective integration in court practices. Religious courts achieved a 96.45% case clearance rate in 2023, processing 603,512 cases, though substantial challenges persist in harmonizing religious and state law (71.8% agreement). The study concludes that while structural frameworks exist for integration, substantive implementation requires enhanced judicial capacity, clearer legislative guidelines, and stronger institutional mechanisms to realize Pancasila's justice principles within Islamic family law adjudication